Skills for communicating with patients - Silverman, Jonathan, Dr (Radcliffe Publishing, 2013)
The Third Edition is one of two companion books on improving communication in medicine which together provide a comprehensive approach to teaching and learning communication skills throughout all levels of medical education in both specialist and family medicine. Since their publication, the first edition of this book and its companion, Teaching and Learning Communication Skills in Medicine, have become texts in communication skills teaching. This substantially expanded third edition has been fully updated in relation to the current literature and revised to reflect the explosion of research on healthcare communication since the second edition was published in 2004. It incorporates considerable evidence in support of the skills of the Calgary-Cambridge Guides, offering a comprehensive and now even more evidence-based delineation of the skills that make a difference when communicating with patients. It explores the specific skills of doctor-patient communication and provides wide-ranging evidence of the improvement that those skills can make to health outcome and everyday clinical practice. It is unique in providing a secure platform of core skills which represent the foundations of doctor-patient communication.